Memory bias toward emotional information in burnout and depression. (September 2020) - Bianchi, Renzo; Laurent, Eric; Schonfeld, Irvin Sam; Bietti, Lucas M; Mayor, Eric
A sample of 1015 educational staff members, exhibiting various levels of burnout and depressive symptoms, underwent a memory test involving incident encoding of positive and negative words and a free recall task. Burnout and depression were each found to be associated with increased recall of negative items and decreased recall of positive items. Results remained statistically significant when controlling for history of depressive disorders. Burnout and depression were not related to mistakes in the reported words, or to the overall number of recalled words. This study suggests that burnout and depression overlap in terms of memory biases toward emotional information.